Mengurai Paradigma Pemikiran Gerakan Islamisme dan Pos-Islamisme di Era Kontemporer - Fauzi, M. Nur (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
This article discusses the paradigm of thought of Islam transnational movement to spread its ideas and discourse in the public sphere. The Islamic transnational movement on this research focused on Islamism and Post Islamism. The research tries to answer a few questions the idea and discourse, shifting paradigm of idea and discourse from Islamism to Post Islamism, and its response to the discourse that grow up from Western civilization. This research founded that it is significant of Islamic shifting paradigm from both Islamic movements. At last, the shifting of the Islamic paradigm caused the differences of thought to respond to the discourse from western modern civilization. From that different paradigm thought of the both contemporary Islamic movement has a result the difference of the product of thought and dichotomic-dualistic too. Islamisms so far reject the ideas and discourse from the Western civilization, meanwhile, Post Islamism more appreciate, accept, and critically.